Factores de riesgos relacionados a la preeclampsia en gestantes atendidas en consulta externa de ginecología en el Hospital General Martin Icaza, periodo abril-agosto 2024. - Mite Franco, Sheyla Dayana (2024)
Objective: To determine the risk factors related to preeclampsia and pregnancy in pregnant women attended in gynecology outpatient clinic at the Hospital General Martin Icaza, period April-August 2024. Materials and methods: The study examined 85 medical records of women with preeclampsia attended between April and August 2024 at the Hospital General Martin Icaza, using a method of selection by convenience, including the nursing staff of the gynecology area and a mixed, descriptive, field, non-experimental, cross-sectional research was used, and structured scientific observation was used to collect and analyze clinical data. Results: In the study of 85 pregnant women, almost half of them were between 30 and 35 years old, this being the most affected age group. Most of them came from urban areas (69%) and had incomes ranging between 310 and 460 dollars per month; in addition, 56% were single. In terms of education, 66% have completed primary school and 75% consider themselves to be of mixed race. The most prevalent symptoms are headache (78%) and foot edema (68%). Most presented slightly elevated blood pressure and 81% showed severe proteinuria. Most are in the late stages of pregnancy and have a history of hypertension, preeclampsia and gestational diabetes. In terms of parity, 52% were nulliparous, and in terms of nutritional status, 38% were overweight. Sixty-six percent attended fewer than 6 prenatal check-ups, while 74% did not consume harmful substances and 87% experienced a high level of stress. All women with preeclampsia received magnesium sulfate treatment and constant monitoring, and 71% participated in comprehensive educational programs. Conclusions: The study revealed that pregnant women with preeclampsia present risk factors such as age, parity and obesity, with higher incidence among women aged 30 to 35 years. Nulliparity, obesity and low socioeconomic status, together with insufficient attendance to prenatal check-ups, aggravate the risk and complications of the disease.